1969
DOI: 10.1016/s0006-3495(69)86366-6
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Changes in the Fluorescence Yield of Chlorophyll a In Vivo

Abstract: The fluorescence transient of Chlorella pyrenoidosa, excited by saturating blue light, has a base level O, hump I, dip D, peak P, and at 1.5 sec a quasi-steady level S (12). With 2 sec exciting exposures and 4 min dark periods, preillumination-1 (lambda >/= 690 nm, intensities 1-750 ergs/sec-cm(2) incident), replacing the dark periods, lowers I more effectively than preillumination-2 (650 nm Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The variable Chl fluorescence increase from I to P represents the measure of electron transport from Q B beyond PSI (Munday and Govindjee 1969 ; Schansker et al 2003 ). As is evident by the values of the probability with which the electron moves toward PSI end acceptors, ψ RE1o , the electron transport between PSII and PSI after HL treatment becomes less limited (Table 4 ), especially in shade leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The variable Chl fluorescence increase from I to P represents the measure of electron transport from Q B beyond PSI (Munday and Govindjee 1969 ; Schansker et al 2003 ). As is evident by the values of the probability with which the electron moves toward PSI end acceptors, ψ RE1o , the electron transport between PSII and PSI after HL treatment becomes less limited (Table 4 ), especially in shade leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence-transient measurements were made as described by Munday and Govindjee (1969). The photomultiplier signal was fed through a Tektronix oscilloscope (type 501) and displayed on an Esterline Angus (model E 11015) or a Midwestern oscillograph recorder (model 801).…”
Section: Methodsmentioning
confidence: 99%
“…1). This slow rise and subsequent decline have been attributed to the reduction and subsequent oxidation of PSII reaction centers (24). The fluorescence data indicated that PSII was not functional during early greening and that delayed PSII assembly could be the basis for the high fluorescence yield.…”
Section: Resultsmentioning
confidence: 98%